Adapting to the Digital Classroom: Challenges and Opportunities for Faculty in Higher Education - V. Bedre, Rupali; Prabhakar Jamnekar, Pallavi; Kumar Yadavalli, Pavan; Borah, Debojit; Biswas, Mahua; Rani S, Kavitha (Journal of Neonatal Surgery, 2025)
The transition to digital classrooms has reshaped teaching and learning dynamics in higher education, presenting unique challenges and opportunities for faculty. This study examines faculty adaptation to online teaching, focusing on engagement strategies, digital competency, and institutional support. Using a mixed-methods approach, survey data were collected from 200 faculty members across public and private institutions, capturing quantitative insights on perceived challenges and qualitative perspectives on adaptation experiences. Results indicate significant challenges in maintaining student engagement, with 67% of respondents noting reduced interaction in virtual settings. Additionally, 47% reported limited digital proficiency, highlighting a need for targeted training programs. The findings further reveal disparities in resource access, with public institutions facing more constraints than private counterparts, underscoring the importance of equitable institutional support. Notably, 78% of faculty acknowledged the benefits of flexible content delivery in digital classrooms, allowing for more inclusive and self-paced learning. The study concludes that while digital classrooms offer promising educational opportunities, effective adaptation requires comprehensive support systems, including enhanced digital literacy training and adjustments to faculty workload. Addressing these factors can empower faculty to deliver high-quality online education and improve student outcomes. This research contributes to the growing literature on digital pedagogy by identifying essential support mechanisms to facilitate successful adaptation in higher education.